2005
DOI: 10.1016/j.cub.2005.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin-Dependent Photoreception Provides Earliest Light Detection in the Mammalian Retina

Abstract: The findings suggest that the non-image-forming pathway is functional long before the mainstream image-forming pathway during development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
181
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(196 citation statements)
references
References 49 publications
13
181
0
2
Order By: Relevance
“…Because mammalian TRPC channels are homologous to the TRP and TRP-like channels that mediate the lightactivated depolarizing responses of Drosophila photoreceptors (Minke and Parnas, 2006;Ramsey et al, 2006), these studies lend support to the hypothesis that melanopsin-related phototransduction may share a number of characteristics common to invertebrate light signaling pathways (Peirson and Foster, 2006;Berson, 2007). A hallmark of Drosophila TRP and TRP-like channels is a high permeability to Ca 2ϩ (Reuss et al, 1997), and consistent with the putative similarities between mammalian ipRGCs and Drosophila photoreceptors, it has been reported that light stimulates an increase in the intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in ipRGC somata (Sekaran et al, 2003(Sekaran et al, , 2005. However, it has yet to be determined whether ipRGC Ca 2ϩ responses result primarily from the direct flux of this cation through the light-gated channel (such as a TRPC channel).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Because mammalian TRPC channels are homologous to the TRP and TRP-like channels that mediate the lightactivated depolarizing responses of Drosophila photoreceptors (Minke and Parnas, 2006;Ramsey et al, 2006), these studies lend support to the hypothesis that melanopsin-related phototransduction may share a number of characteristics common to invertebrate light signaling pathways (Peirson and Foster, 2006;Berson, 2007). A hallmark of Drosophila TRP and TRP-like channels is a high permeability to Ca 2ϩ (Reuss et al, 1997), and consistent with the putative similarities between mammalian ipRGCs and Drosophila photoreceptors, it has been reported that light stimulates an increase in the intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in ipRGC somata (Sekaran et al, 2003(Sekaran et al, , 2005. However, it has yet to be determined whether ipRGC Ca 2ϩ responses result primarily from the direct flux of this cation through the light-gated channel (such as a TRPC channel).…”
Section: Introductionsupporting
confidence: 66%
“…Long-Evans rats (4 -6 per session) were killed on postnatal day 5 (P5)-P7 by halothane overexposure and decapitation. At this neonatal age, rat (Hannibal and Fahrenkrug, 2004b) and mouse (Sekaran et al, 2005) ipRGCs have been shown previously to be light responsive. After enucleation, the retinas were dissected in Hibernate-A medium (BrainBits, Springfield, IL) with 2% B27 supplements (Invitrogen, Carlsbad, CA) and 10 g/ml gentamicin.…”
Section: Methodsmentioning
confidence: 63%
“…Physiologically, in mouse retina, melanopsin-expressing ipRGCs can be activated by light as early as the day of birth (9,10). Concomitantly, by postnatal day 1 (P1), ipRGCs express vesicular glutamate transporter type 2, necessary for the synaptic release of glutamate from ipRGCs (11), and project their axons to the suprachiasmatic nucleus (SCN) of the hypothalamus (12).…”
mentioning
confidence: 99%
“…Concomitantly, by postnatal day 1 (P1), ipRGCs express vesicular glutamate transporter type 2, necessary for the synaptic release of glutamate from ipRGCs (11), and project their axons to the suprachiasmatic nucleus (SCN) of the hypothalamus (12). Furthermore, the retina-SCN tract in rats can be activated by light immediately after birth (9,10,13).…”
mentioning
confidence: 99%
“…These responses depend on the opsin family member melanopsin (5), which is expressed exclusively in a subset of intrinsically photosensitive retinal ganglion cells (ipRGCs) (6)(7)(8). Mice with nonfunctional or degenerated rods and cones that also lack melanopsin show no photically influenced behavior or physiology (9,10), and intrinsic photosensitivity of retinal ganglion cells is lost in the absence of melanopsin (9,11,12). Melanopsin forms a functional photopigment when heterologously expressed in COS cells (13), Xenopus oocytes (14), Neuro-2A cells (15), or HEK-293 cells (16).…”
mentioning
confidence: 99%